2002
DOI: 10.5089/9781451857245.001
|View full text |Cite
|
Sign up to set email alerts
|

Asian Flu or Wall Street Virus? Price and Volatility Spillovers of the Tech and Non-Tech Sectors in the United States and Asia

Abstract: The views expressed in this Working Paper arc those of the author(s) and do not necessarily represent those of the IMF or IMF policy. Working Papers describe research in progress by the author(s) and are published to elicit comments and to further debate. This paper, using T -GARCH models, finds that the United States has been the major source of price and volatility spillovers to stock markets in the Asian region during three different periods in the last decade: the pre-Long Term Capital Management crisis pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…First, unlike many existing studies which focus on how a single international market (often the US or a world market) influences other stock markets 4 , we consider the innovations from both the US and Japanese markets in an attempt to analyse the impacts of both regional and world shocks on South Asian equities. Second, we recognise that volatility transmission may be asymmetric in 3 See, Ng (2000), Chan-Lau and Ivaschenko (2002) and Worthington and Higgs (2004) for some evidence on this topic. 4 Many early studies failed to distinguish between world and regional factors as they were predominantly occupied with testing the influence of the world market (often US) on other markets.…”
Section: Introductionmentioning
confidence: 95%
“…First, unlike many existing studies which focus on how a single international market (often the US or a world market) influences other stock markets 4 , we consider the innovations from both the US and Japanese markets in an attempt to analyse the impacts of both regional and world shocks on South Asian equities. Second, we recognise that volatility transmission may be asymmetric in 3 See, Ng (2000), Chan-Lau and Ivaschenko (2002) and Worthington and Higgs (2004) for some evidence on this topic. 4 Many early studies failed to distinguish between world and regional factors as they were predominantly occupied with testing the influence of the world market (often US) on other markets.…”
Section: Introductionmentioning
confidence: 95%
“…An extensive strand of this literature, particularly relevant to our chapter, has documented how the United States is a major source of spillovers to financial markets around the globe (Ng, 2000;and Chan-Lau and Ivaschenko, 2003). Arora and Cerisola (2001) show that the stance and predictability of U.S. monetary policy influence country risk, proxied by sovereign bond spreads, because both factors are important determinants of economic growth in developing countries.…”
Section: Related Literaturementioning
confidence: 99%
“…An extensive strand of this literature, particularly relevant to our paper, has documented how the United States is a major source of spillovers to financial markets around the globe (Ng(2000), andChan-Lau andIvaschenko (2002)). Arora and Cerisola (2000) showed that the stance and predictability of U.S. monetary policy influences country risk, proxied by sovereign bond spreads, as they are important determinants of economic growth in developing countries.…”
Section: Related Literaturementioning
confidence: 99%